Penerapan Algoritma Mixed Heuristic dalam Penilaian Ujian Pada Jurusan Pendidikan Teknik Elektro Universitas Negeri Medan - Sari, Ressy Dwitias; Rahmadani, Reni (MEANS (Media Informasi Analisa dan Sistem), 2020)
During the COVID-19 pandemic, teaching and learning activities switch of technology such as e-learning. In the Department of Electrical Engineering Education, Universitas Negeri Medan, 80% of electrical lecturers provide multiple choice exams and short answers. The scoring system cannot be performed automatically by a computer. The algorithm used in this study is a Mixed Heuristic algorithm. This algorithm is used because it is an effective way of working for sentences of more than 1 word. And give the results in the form of ranking in the form of similarity proportions. From the process of using a mixed heuristic algorithm, it can be proven that this algorithm can perform keywords on the answer keys and answers of users or students. The algorithm is also able to provide value to a user or student's answers